Speech and hearing science in ancient India: a survey of sanskrit literature - SR, Savithri (Journal of All India Institute of Speech and Hearing)
In the context of an awareness of a lack of coordinated information and of a renewed interest in Ayurveda and Sanskrit literature the present study was undertaken. The intention of this study was to compile the available information in the Sanskrit literature with respect to the field of Speech and Hearing.